Technology and research on the influence of liquid crystal cladding doped with magnetic Fe3O4 nanoparticles on light propagation in an optical taper sensor - Niewczas, Michał; Stasiewicz, Karol A.; Przybysz, Natalia; Pakuła, Anna; Paczesny, Jan; Zbonikowski, Rafał; Dziaduszek, Jerzy; Kula, Przemysław; Jaroszewicz, Leszek R. (Advanced Optical Technologies, 2024)
The results obtained for new dual-cladding optical fibre tapers surrounded by liquid crystal dopped of Fe3O4 nanoparticles in a specially developed glass cell are presented. The created structures are sensitive to changing refractive index values in a surrounding medium caused by modifying external environment parameters. In this investigation, cells are filled with nematic liquid crystals 6CHBT and with the same mixtures doped with 0.1 wt% and 0.5 wt% of magnetic nanoparticles (Fe3O4 NPs). The taper is made on a standard single-mode telecommunication fibre, stretched out to a length of 20.0 ± 0.5 mm, and the diameter of the tapers is around 15.0 ± 0.3 μm, with a loss lower than 0.5 dB @ 1550 nm. Measurements are executed in a wide range covering the visible and infrared range in two setups: (i) without a magnetic field with steering only by a voltage and (ii) with an applied magnetic field. The presented spectrum results are divided into two ranges according to the parameters of optical spectrum analyzers: 350 -1200 nm and 1200 -2400 nm. For all investigations, a steering voltage is chosen from the range of 0 -200 V, which allows for establishing the influence of dopants on transmitted power and time response at different arrangements. Due to the sensitivity of liquid crystals to temperature changes, the paper focuses on measurement in a room temperature to measure the effect of the magnetic field on propagation in a fiber optic taper. The proposed solution demonstrates the technology for creating advanced components as a combination of fiber optic technology, liquid crystals and nanoparticles. The presented results show the possibility of creating new sensors of various external factors including magnetic or electric fields in miniaturized dimensions.